Effects of age on electrophysiological correlates of speech processing in a dynamic “cocktail-party” situation - Getzmann, Stephan; Hanenberg, Christina; Lewald, Jörg; Falkenstein, Michael; Wascher, Edmund (Frontiers in Neuroscience, 2015)
Successful speech perception in multi-speaker environments depends on auditory scene analysis, comprising auditory object segregation and grouping, and on focusing attention toward the speaker of interest. Changes in speaker settings (e.g., in speaker position) require object re-selection and attention re-focusing. Here, we tested the processing of changes in a realistic multi-speaker scenario in younger and older adults, employing a speech-perception task and event-related potential (ERP) measures. Sequences of short words (combinations of company names and values) were simultaneously presented via four loudspeakers at different locations, and the participants responded to the value of a target company. Voice and position of the speaker of the target information were kept constant for a variable number of trials and then changed. Relative to the pre-change level, changes caused higher error rates, and more so in older than younger adults. The ERP analysis revealed stronger fronto-central N2 and N400 components in younger adults, suggesting a more effective inhibition of concurrent speech stimuli and enhanced language processing. The difference ERPs (post-change minus pre-change) indicated a change-related N400 and late positive complex (LPC) over parietal areas in both groups. Only the older adults showed an additional frontal LPC, suggesting increased allocation of attentional resources after changes in speaker settings. In sum, changes in speaker settings are critical events for speech perception in multi-speaker environments. Especially older persons show deficits that could be based on less flexible inhibitory control and increased distraction.